The role of multiple pollutants and pollution intensities in the policy reform of taxes and standards. - Gautier, Luis (De Gruyter, 2019)
Countries with varying degrees of pollution intensities, facing increasing global competition and addressing emissions from multiple pollutants may undertake policy reforms inconsistent with cooperative outcomes, where global welfare is higher. Among others, this is because of the incentives to set laxer policy to be more cost competitive. A number of welfare-enhancing and emissions-reducing policy reforms consistent with the cooperative equilibrium, but also consistent with addressing concerns about global competitiveness are derived. The analysis indicates that the nature of multiple pollutants and asymmetries in pollution intensities are key in the design of policy reform and characterization of optimal policy. With complementarity and asymmetry in pollution intensities, laxer taxation and stricter standards are consistent with welfare gains. Laxer taxation arises with large asymmetry in pollution intensities regardless of whether pollutants are complements/substitutes. The policy reform of standards requires both complementarity and asymmetry in pollution intensities. Results are reversed if pollutants are substitutes.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/19218
Keywords: Contaminación; Impuestos ambientales; Política ambiental; Policy reform; Multiple pollutants; Emission tax; Environmental standards; Pollution intensity; Heterogeneous abatement costs